2007
DOI: 10.1007/s00254-007-0957-6
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dynamics in large shallow eutrophic Lake Chaohu, China

Abstract: Temporal and spatial dynamics of nitrogen in lake and interstitial water were studied monthly in a large shallow, eutrophic lake in subtropical China from October 2002 to September 2003. The distribution of nitrogen was consistent with the idea that high nitrogen concentrations in the western part of the lake resulted from high levels of the nutrients from the surrounding cities through sewagedrainage systems. Nitrate was the predominant form of nitrogen in the overlying water, while ammonium was predominant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 43 publications
0
14
0
3
Order By: Relevance
“…The significant correlations in the observed MTL with the annual mean phosphorus concentrations and nitrogen/phosphorus ratios in recent decades clearly indicate that the phosphorus input (via sewage discharge from urban and rural areas) strongly impact the community structure and functioning in Lake Chaohu (Xu et al, 2005(Xu et al, , 2007aZhang et al, 2008). This leads to an imbalance of whole-ecosystem primary production (benthic and pelagic), i.e., a loss of benthic production, and a shift toward pelagic primary production, as noted in other ecosystems affected by eutrophication (Takahashi et al, 1990;Schindler and Scheuerell, 2002;Vander Zanden and Vadeboncoeur, 2002;Vadeboncoeur et al, 2003).…”
Section: Environmental Impacts On the Ecosystemmentioning
confidence: 96%
“…The significant correlations in the observed MTL with the annual mean phosphorus concentrations and nitrogen/phosphorus ratios in recent decades clearly indicate that the phosphorus input (via sewage discharge from urban and rural areas) strongly impact the community structure and functioning in Lake Chaohu (Xu et al, 2005(Xu et al, , 2007aZhang et al, 2008). This leads to an imbalance of whole-ecosystem primary production (benthic and pelagic), i.e., a loss of benthic production, and a shift toward pelagic primary production, as noted in other ecosystems affected by eutrophication (Takahashi et al, 1990;Schindler and Scheuerell, 2002;Vander Zanden and Vadeboncoeur, 2002;Vadeboncoeur et al, 2003).…”
Section: Environmental Impacts On the Ecosystemmentioning
confidence: 96%
“…David et al () found that denitrification in an agricultural reservoir in the midwestern U.S. Corn Belt could remove 60,900 Mg N/year, while Havens and James () found that an average of 297 Mg P/year was retained in an agricultural lake in Florida. Although reservoirs can sequester large amounts of N and P in lakebed sediments, retention in sediments can be highly variable with total N (TN) concentrations ranging from <500 to 12,000 mg/kg and total P (TP) concentrations ranging from <200 to 2,000 mg/kg (Pearce et al, ; Pulatsü et al, ; Xu et al, ; Zhang et al, ). Despite this variability in nutrient retention efficiently, reservoirs and lakes decrease the overall magnitude and interannual variability of river mass exports (Powers et al, ; Powers et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Before the 1950s, it was well known for its scenic beauty and richness of aquatic life. However, the lake is currently facing a threat of serious eutrophication (Zhang et al, 2008). Every year during warm season, dense cyanobacterial blooms (mainly composed of genus Microcystis and genus Anabaena ) are observed in the lake (Xu et al, 2007).…”
Section: Study Site and Sampling Methodsmentioning
confidence: 99%